A survey on the information needs and uses of research staff and researchers at the Philippine Institute for Development Studies (PIDS) with implications for library collection development - Tolentino, Valentina V.; Buenviaje, Rufo Q. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1986)
This study was conducted to determine the information needs of the research staff and researchers of the Philippine Institute for Development Studies (PIDS) and the implications of such needs to serve as a guide to collection development for the Institute's Library. It aimed to identify specific needs for information as well as the problems, purposes for which information is sought, the sources of information, subject areas and titles of periodicals for which the library must build its collection.
The normative and descriptive survey method of research, using the questionnaire as a tool in gathering data, was used in this study. A total of 40 out of 50 respondents answered the questionnaires.
The major findings of the study are: 1) the respondents devoted 91.43 percent of their time to research and development activity; 2) one third of the respondents have the experience in scholarly writing/conducting research and have an average publication output of 3.05 each per year; and, 3) 87.5 percent used the library regularly.
The major purposes in seeking information were mostly in connection with their research activity: to get specific information needed for work in progress; to keep informed of development in one's field; and to provide introductory background information for new work in unfamiliar fields. The types of information needed by the respondents for their research work are statistics, general background information, specific information on theories and bibliographic information. The information needs and uses of their research staff have major implications for the development of the PIDS library collection. Their preferred subject areas of interest and their suggestions on titles of periodicals to be procured imply that the library has a lot to do to provide adequate basic references and current materials for their research work.
The study recommends that: 1) There is a need to keep the collection current to anticipate staff information needs that can be met through pertinent reference materials; 2) Improve the collection by acquiring more materials of direct concern to PIDS activities; 3) Subscribe immediately to journals and other related periodicals suggested in this study; 4) Catalog and index the resources for easy access; 5) Suggest or encourage staff to turn over materials obtained from book allowances to the library; 6) Centralize request for procurement of reading materials rather than obtaining them individually, thus making the materials available to all and avoiding duplication for the benefit of the Institute; 7) Provide wider space for the user and working area for the staff to fully accomplish its various activities such as cataloging, indexing, filing, typing, etc.; 8) A photocopying machine and computer hardware should be acquired for the library and Research Information Department use only; 9) Obtain or develop own database management which could be used for storage and retrieval of bibliographic records; 10) Provide a continuing manpower training program for information and library personnel to enable them to keep up with developments in the field; 11) There is also a need to strengthen the interlibrary loan relations between other special libraries and PIDS library and to maintain good working relationships with them which consequently will enrich the Institute's Library collection with valuable materials.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Information services -- Philippine Institute for Development Studies; Libraries -- Collection development Philippine Institute for Development Studies; Information services -- Philippine Institute for Development Studies; Libraries -- Collection development; Philippine Institute for Development Studies